Architekturwissenschaft. Vom Suffix zur Agenda - Almarza Anwandter, Juan; Bovelet, Jan; Dürfeld, Michael; Froschauer, Eva Maria; Neubert, Christine; Schneider, Peter I.; Weckherlin, Gernot (Forum Architekturwissenschaft, 2021)
What is `Architekturwissenschaft´? This publication presents various aspects concerning the connection of `Wissenschaft´ - including both science and humanties - and Architecture demonstrating the significance of the former to the latter and vice versa. In reflecting their interrelation, the perspectives of the different contributions are directed either to the past, to the present situation or to the future of an insitutionalised `Architecturewissenschaft´.